The Effect of Education Variable on the Open Unemployment Rate - Rahmawati, Anik; Putri, Phany Ineke (Efficient: Indonesian Journal of Development Economics, 2021)
This study aimed to determine and analyze the effect of literacy rate, government expenditure on education, Gross Enrollment Rate of Senior High School/equivalent, and the proportion of Senior High School workforce and above on Open Unemployment Rate. The type of data used was secondary data. In form of panel data (pooled data) which is a combination of cross section data from eight regencies/cities in Banten Province and time series data from 2010-2019. The analysis method used was panel data regression analysis. The best model chosen was the Fixed Effect Model (FEM). The results showed that the variable literacy rate did not have any significant and negative effect on TPT. The variable government expenditure on education had a significant and negative effect on TPT. The variable Gross Enrollment Rate of Senior High School/Equivalent had a significant and negative effect on TPT. The variable proportion of Senior High School workforce and above had a significant and negative effect on TPT Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh angka melek huruf, pengeluaran pemerintah bidang pendidikan, Angka Partisipasi Kasar SMA/Sederajat, dan proporsi angkatan kerja SMA ke atas terhadap Tingkat Pengangguran Terbuka (TPT). Jenis data yang digunakan adalah data sekunder. Tipe data yang digunakan adalah data panel (pooled data), yang merupakan kombinasi data cross section delapan kabupaten/kota di Provinsi Banten dan data time series tahun 2010-2019. Metode analisis yang digunakan adalah analisis regresi data panel. Model terbaik yang terpilih adalah Fixed Effect Model (FEM). Hasil penelitian menunjukkan bahwa variabel angka melek huruf tidak berpengaruh signifikan dan negatif terhadap TPT. Variabel pengeluaran pemerintah bidang pendidikan berpengaruh signifikan dan negatif terhadap TPT. Variabel Angka Partisipasi Kasar SMA/Sederajat berpengaruh signifikan dan negatif terhadap TPT. Variabel proporsi angkatan kerja SMA ke atas berpengaruh signifikan dan negatif terhadap TPT.